Effect of systematic oral nursing interventions on dental plaque control and oral health care behavior in patients with periodontal disease (系统口腔护理干预对牙周病患者牙菌斑控制效果及口腔保健行为的影响) - CAI Shuang (蔡爽); LIU Xuewei (刘学伟); WANG Meng (王蒙); CUI Yue (崔悦); WANG Wei (王威) (Association of Integrative Nursing, 2024)
Objective To explore the effect of systematic oral care interventions on dental plaque control and oral health care behavior in patients with periodontal disease. Methods From March 2022 to April 2023, 100 patients with periodontal disease were divided into the control group and observation group by drawing-lots method. The control group(n=50) received routine nursing interventions, and the observation group(n=50) received systematic oral nursing intervention. The effect of interventions on dental plaque control and oral health care behavior was evaluated and compared between two groups. Results After 3 months of nursing interventions, the gingival bleeding index, periodontal pocket probing depth and dental plaque index in the observation group were lower than those in the control group, with a significant difference (P＜0. 01). The qualified rate of oral health care behavior in observation group was higher than that in control group (P＜0. 01). The hospital revisit rate, correct answer fill rate of oral health care knowledge questionnaire, compliance rate of oral health care behavior in the observation group were higher than those in control group (P＜0. 01). Conclusion The implementation of systematic oral nursing interventions can improve the effect of plaque control and the qualified rate of oral health care behavior in patients with periodontal disease. (目的 研究系统口腔护理干预对牙周病患者牙菌斑控制效果及口腔保健行为的影响。方法 选取2022年3月-2023年4月医院收治100例牙周病患者为研究对象, 经抽签法分为对照组和观察组, 每组50例。对照组实施常规护理干预, 观察组实施系统口腔护理干预。评估两组牙菌斑控制效果和口腔保健行为。结果 护理3个月后, 观察组牙龈出血指数、牙周袋探诊深度、牙菌斑指数低于对照组, 差异有统计学意义(P＜0. 01)。观察组口腔保健行为达标率高于对照组(P＜0. 01)。观察组患者按时复诊率、口腔卫生健康知识回答正确率、口腔卫生习惯依从性均高于对照组(P＜0. 01)。结论 牙周病患者实施系统口腔护理干预, 可提高牙菌斑控制效果及口腔保健行为达标率, 值得临床借鉴。)